Inherent Acts of Self-determination: Administrative Control of Elementary Education at Six Nations, 1960-2005 - Staats, Jesse A. (2021)
I collaborate with Elders of the Six Nations of the Grand River Territory – mainly former vice-principals and principals – to share their stories about elementary school administration of the community’s day schools of the 1960s, 70s, and 80s, and of the larger consolidated schools thereafter. By engaging in storywork with them, their stories reveal that as Indigenous organizations like the National Indian Brotherhood/Assembly of First Nations (NIB/AFN) warned First Nations about mistaking administrative control, or delegated authority as it framed it, as real, local control over their children’s education, vice-principals and principals in Six Nations reframed it as inherent acts of self-determination and sovereignty over education. Drawing on Audra Simpson’s nested sovereignty, and Glen Sean Coulthard’s self-recognition to produce a more accurate representation of administrative control in the community, the author argues that vice-principals and principals in Six Nations did not mistake their practice as delegated authority but instead – as inherently sovereign actors – went through a process of negotiating self-determination and sovereignty within the Department of Indian Affairs and Northern Development Canada’s (DIAND) educational framework to upset its status quo of First Nations only managing educational programs and services. If sovereignty is understood to be a process, rather than a destination as Robert Allen Warrior suggests, then vice-principals and principals exercising administrative control on a daily basis in their schools should be recognized as inherently self-determining and sovereign. By sharing their stories, they reveal that they possess the authority to determine the definition and character of administrative control at the local level. The argument’s implication being that there are alternative ways of knowing and understanding administrative control in First Nations schools, rather than the national discourse that evolved in the decades following the NIB’s Indian Control of Indian ...